Socialization and Education about Paylater and Online Loans for Vocational Students in Order to Reduce Hedonistic Behavior - Putri Syuhada; Een Mardiyanti; Agus Firmansyah; Suri Purnami; Haris Pinagaran Nasution; Teddy Prasetyo (ALTSA Publisher, 2024)
Socialization and Education About Paylater and Online Loans at Tarbiyah Islamiyah Private Vocational Schools to Reduce Hedonistic Behavior aims to provide education about paylater, online loans, using social media wisely and managing healthy finances. In order to run PMKM activities smoothly, the service team conducted a data collection technique by interviewing the Tarbiyah Islamiyah Private Vocational School. The solution provided is to find knowledge transfer through seminars on Socialization and Education about Paylater and Online Loans at Tarbiyah Islamiyah Private Vocational Schools to reduce hedonistic behavior. The cost of implementing PMKM activities is needed at Rp.1,500,000 (one million five hundred thousand rupiah) and requires physical facilities such as infocus, Mic, Speaker and certificates for schools and students of Tarbiyah Islamiyah Private Vocational School. After carrying out community service activities in the form of training and seminars to students, the results of the service were obtained that: Challenges in educating students about the negative impact of paylater, the dangers of online loans , hedonistic behavior, and the importance of implementing healthy financial behavior, such as saving, at Tarbiyah Islamiyah Private Vocational School, have been overcome with interesting and interactive educational activities. This activity includes providing an understanding of the risks of using paylater and loans, the impact of hedonistic behavior in finance, and the importance of saving early as a step to manage finances wisely. One of the programs carried out is personal financial management and healthy financial planning training, which aims to form a positive mindset towards money and wise use of financial services. This educational activity has succeeded in increasing students' understanding of the importance of having healthy financial behavior with an average knowledge achievement result of 94% in paylater material, 91% in loan material, 87% in hedonism material, and 66% in healthy financial behavior material. However, the absence of a program that specifically addresses the threat of the dangers of consumptive behavior such as hedonism and the long-term impact of the use of paylater and loans is a challenge that needs to be overcome further. With a fun and creative approach, it is hoped that this educational activity can continue to expand awareness among students about the importance of wise financial management, as well as encourage them to be more active in implementing healthy financial behaviors, such as saving, in order to maintain their economic well-being in the future.